USING MULTIMEDIA AND WEB TECHNOLOGIES IN STUDYING THE HUMANITIES. WEB-MULTIMEDIA ENCYCLOPEDIA «WILLIAM SHAKESPEARE AND RENAISSANCE» - Alferov Є.А. (Journal of Information Technologies in Education (ITE), 2010)
The article discusses the use of innovative information technologies in modern education. Special attention is given to the using of web-multimedia technologies in the study of humanities. As an example of using information and communication tools in the process of philological disciplines described purpose, functionality and architecture of web-multimedia encyclopedia «William Shakespeare and Renaissance» (http://shakespeare.ksu.ks.ua), developed in laboratory of the integrated learning environments of the Research Institute of IT.